A Study on the Rules for the Recognition of Surrogate Paternity in China - Xiaoteng Cao (Law and Economy, 2022)
In the context of surrogacy using artificial reproductive technology, the identity of genetic mother, birthing mother, and legal mother are separated, leading to difficulties in the determining paternity. In China, surrogacy contracts are invalid because they are against public order and morality and may not be used as the basis for paternity determination. Among the doctrines on the determination of surrogate paternity, the birth theory ignores the genetic link, the bloodline theory ignores the fact of conception, the contract theory is against China’s position, and the best interest of the child theory is too open. In light of the actual situation in China, the determination of surrogate paternity should be based on the principle of biological connection and social connection, and the relevant rules should be applied flexibly in accordance with the specific circumstances of the case.